Analysis of acoustic oceanographic data characterizing tidal and non-tidal current flux in a gulf–basin system - Omar A. Nimr; Ramy Y. Marmoush; Mohamed A. Oraby; Ahmed Gaweesh; Ahmed Balah; Darrell W. S. Tang (Frontiers in Marine Science, 2026)
Coastal currents arise from the combined influence of tidal and non-tidal processes such as wind forcing, density gradients, and Earth’s rotation. This study quantifies their relative contributions in the Gulf of Aqaba using velocity records from 10 Acoustic Doppler Current Profilers (ADCPs) deployed along the eastern shallow-water coast during April and May 2021. Harmonic least-squares analysis was used to separate the astronomical tidal current from the residual, and tidal form factors and rotary analysis characterized the tidal type and the ellipse properties of the principal constituents (M2, S2, K1, and O1). Non-tidal currents dominated throughout the study period, with the tidal-to-non-tidal speed ratio below unity at every station except one and a mean of 0.59. Tidal form factors classify the regime as mixed at almost all stations, with dominant contributions from the M2 and K1 constituents. Depth-averaged tidal ellipses are predominantly rectilinear and show marked spatial variability in speed and orientation, with the strongest currents where the coast narrows. Correlations between wind stress and the residual currents are moderate and organized predominantly along the coast, indicating that wind is a meaningful but partial driver, with much of the residual variability set by processes a local wind correlation cannot capture. These findings establish the predominance of non-tidal forcing in the coastal circulation of the Gulf of Aqaba and highlight the need for extended, co-located current and hydrographic records to resolve the full range of forcing in semi-enclosed stratified basins.